ONLINE TAXIBIKE (GRAB) CONTRIBUTION IN COMMUNITY SERVICE IN MALANG DISTRICT - Moh Khoirul Anam; saifuddin saifuddin; Sulis Nada Fitriah (Nurul Jadid University, 2022)
Taxibike (grab) is a pick-up service with a modern, order-based Taxibike. Taxibike is a two-wheeled motor vehicle that is a very effective transportation.This application allows users who can order Taxibike online. Also known as a modern and professional Taxibike. The purpose of this study was to determine the contribution of online Taxibike in public services in Malang Regency. This research is a qualitative research with a qualitative description approach. The purpose of this research is to examine natural objects, to get an overview of the development of the transportation industry and the contribution of online Taxibike to public service in Indonesia, especially the Grab company. The results of this study indicate that the contribution of this online transportation application work system has a major impact on improving driver performance and is very beneficial for consumers and drivers of online transportation companies. Also this online Taxibike is a breakthrough in online business which is currently in demand by the Indonesian people, especially in the Malang district.